Ethical safety of deep brain stimulation: A study on moral decision-making in Parkinson's disease. Issue 7 (July 2015) - Fumagalli, Manuela; Marceglia, Sara; Cogiamanian, Filippo; Ardolino, Gianluca; Picascia, Marta; Barbieri, Sergio; Pravettoni, Gabriella; Pacchetti, Claudio; Priori, Alberto
Abstract Introduction The possibility that deep brain stimulation (DBS) in Parkinson's disease (PD) alters patients' decisions and actions, even temporarily, raises important clinical, ethical and legal questions. Abnormal moral decision-making can lead to ethical rules violations. Previous experiments demonstrated the subthalamic (STN) activation during moral decision-making. Here we aim to study whether STN DBS can affect moral decision-making in PD patients. Methods Eleven patients with PD and bilateral STN DBS implant performed a computerized moral task in ON and OFF stimulation conditions. A control group of PD patients without DBS implant performed the same experimental protocol. All patients underwent motor, cognitive and psychological assessments. Results STN stimulation was not able to modify neither reaction times nor responses to moral task both when we compared the ON and the OFF state in the same patient (reaction times, p = .416) and when we compared DBS patients with those treated only with the best medical treatment (reaction times: p = .408, responses: p = .776). Conclusions Moral judgment is the result of a complex process, requiring cognitive executive functions, problem-solving, anticipations of consequences of an action, conflict processing, emotional evaluation of context and of possible outcomes, and involving different brain areas and neural circuits. Our data show that STN DBS leaves unaffected moral decisions thus implying relevant clinical and ethical implications for DBS consequences on patients' behavior, on decision-making and on judgment ability. In conclusion, the technique can be considered safe on moral behavior.